1996
DOI: 10.1002/j.1550-8528.1996.tb00528.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Intraduodenally Administered Enterostatin in Rats: Inhibition of Food

Abstract: MEl, JIE AND CHARLOTTE ERLANSON-ALBERTSSON. Role of intraduodenally administered enterostatin in rats: inhibition of food intake. Obes Res. 1996;4:161-165. . Central and peripheral administration of enterostatin have been reported to reduce fat or high-fat food intake in rats. Enterostatin is formed in the intestinal lumen by tryptic cleavage of pancreatic procolipase during intraluminal fat digestion. The present experiments were designed to test if enterostatin following intraintestinal infusion would affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Since enterostatin as well as its precursor molecule procolipase increased with high-fat diet it was suggested to act as a negative feedback regulator during fat intake [4]. The anorectic effect, originally observed after central and peripheral injection, was also observed after intra-intestinal administration, hence at a site where enterostatin is also produced [9,10]. For the transmission of the satiety effect of enterostatin intact vagus afferent innervation was important [11].…”
Section: Enterostatin -A Peptide Released From Procolipase During Fatmentioning
confidence: 99%
“…Since enterostatin as well as its precursor molecule procolipase increased with high-fat diet it was suggested to act as a negative feedback regulator during fat intake [4]. The anorectic effect, originally observed after central and peripheral injection, was also observed after intra-intestinal administration, hence at a site where enterostatin is also produced [9,10]. For the transmission of the satiety effect of enterostatin intact vagus afferent innervation was important [11].…”
Section: Enterostatin -A Peptide Released From Procolipase During Fatmentioning
confidence: 99%
“…Similarly, enterostatin reduces intake of single diets when the diet is high, but not when it is low, in fat content (36). Enterostatin is effective intragastrically (91) and intraduodenally (48) and by intraperitoneal (38,55,56), intravenous (46), and intracerebroventricular (icv) (36,38,46) routes. With the exception of intravenous administration, when there is a delay in the response of 60 minutes to 120 minutes, the peptide has a rapid effect (<30 minutes) after administration by all other routes.…”
Section: Feeding Response Of Enterostatinmentioning
confidence: 99%
“…The potency of the action of enterostatin is reflected in its long duration of action and its effect on feeding, lasting up to 6 hours after a single injection in rats adapted to a 6-hour feeding schedule (48) or lasting up to 24 hours after a single injection in ad libitum-fed rats (56). During chronic OBESITY RESEARCH Vol.…”
Section: Feeding Response Of Enterostatinmentioning
confidence: 99%
See 1 more Smart Citation
“…The first relates to the site of the CCK-A receptors that modulate the response. After the initial observations that enterostatin given intraperitoneally would inhibit intake of dietary fat (28), localized infusions of enterostatin, initially into the stomach (45) or duodenum (24) and subsequently into the near-celiac artery (12), have suggested that the gastric-proximal duodenum region is a peripheral site of action. Both the procolipase precursor protein and enterostatin have been localized to mucosal layers in this region by using immunohistochemical approaches (23,39).…”
Section: Discussionmentioning
confidence: 99%